Basis for the control of purine biosynthesis by purine ribonucleotides. - Itakura, M (1981)
An animal model was used to determine the basis for the increase in purine biosynthesis that results from hepatic depletion of purine nucleotides, such as seen in patients with type I glycogen storage disease or following fructose administration. Mice were injected intravenously with glucose or fructose, 2.5 mg/g of body weight, and the animals were killed at 0, 3, and 30 min following carbohydrate infusion. Fructose, but not glucose, administration led to a threefold increase in [14C]glycine incorporation into hepatic purine nucleotides documenting an increase in the rate of purine biosynthesis in the liver of fructose-treated animals. In the fructose, but not the glucose-treated animals, there was a reduction in the hepatic content of purine nucleotides that are inhibitory for amidophosphoribosyltransferase, the enzyme that catalyzes the first reaction unique to the pathway of purine biosynthesis. PP-ribose-P, an important metabolite in the control of purine biosynthesis, was increased 2,3-fold in liver following fructose, but not glucose administration. In conjunction with the decrease in inhibitory nucleotides and increase in PP-ribose-P 29% of amidophosphoribosyltransferase was shifted from the large inactive to the small active form of the enzyme. Results of these studies demonstrate that the end-products of the pathway, purine nucleotides, control the activity of the enzyme that catalyzes the first reaction leading to purine nucleotide synthesis either through a direct effect of purine nucleotides on the enzyme, through an indirect effect of the change in nucleotides on PP-ribose-P synthesis, or a combination of these effects. The resultant changes in amidophosphoribosyltransferase conformation and activity provide a basis for understanding the increase in purine biosynthesis that results from hepatic depletion of purine nucleotides.